Exploring Digital Game-based Learning practices in different learning strategies and environments among teachers - Amran, Aryanti (2022)
Industrial Revolution 4.0 (IR 4.0) dimensions are seen benefiting not only in the economic sector but also has gained significant attention in the development of education. This has led Malaysia to Education 4.0, in which the new Digital Malaysia policy is designed to prepare the younger generation to meet 21st-century demands. In line with the development and milestone of Education 4.0, Digital Game-based Learning (DGBL) has been recognized as an approach for new learning by playing game. However, this effort is still at an initial stage in the Malaysian context, and the need for research and development of Game-based Learning that suits Malaysian educational settings is crucial. Therefore, this research aims to comprehensively understand DGBL practises in different learning strategies and how DGBL can be an excellent approach in a more formal educational environment. Three main questions have been set in this research to be investigated, and they are: 1) How does teacher utilise DGBL? 2) How does learning takes place in DGBL? 3) What aspects of the game contribute to teachers' implementation of the DGBL? Based on studies carried out in past research on emerging technology for learning, it was found that DGBL has gained much attention as an approach to learning that needs a deeper study. Theories underpinning this research are experiential learning theories by David Kolb and Zone of Proximal Development (ZPD) by Vygotsky. All these theories were immersed in the model of Game-based Learning introduced by Garris (2002). This study employs snowball sampling techniques which the number is growing through the recommendation of the participant to others who share the same interest and practises in DGBL in a specific community group or event. Participants have similar criteria - teachers that use DGBL actively in the classroom. The numbers of informants shall depend on teacher’s suggestion of the one with the same criteria, starting by the first person and evolving until the data saturated. This qualitative research is employing a case study design and the technique of data collection was semi-structured interviews. The data were analyzed using Atlas.ti 9 software to obtain codes, categories and subthemes and subsequently established the main theme to answer each research question. The audit trail methods and colleagues' examinations are used to obtain validity and reliability. The Research Questions (RQs) were set to represent different focuses in teaching and learning of using game – Teaching, Learning and Technology (Game). RQ1 represents the perspective of teachers which covers for the context of Teaching. In this context there are four themes emerged from the RQ1. RQ2 represents the perspective of students which covers of the context of Learning where there are six main themes that emerged from the analysis. RQ3 represents the perspective of technology which covers of the context of Game. In this context, as many as five themes were formed. All the three contexts (Teaching, Learning and Game) are connected to each other to promote the best learning strategies, teaching strategies and better learning environment in improving current practises through implementation of new approach of DGBL integration. In the situation like during pandemic, requires students to learn remotely which this method can serve as an alternative method of learning and attracting students to learn in a fun way through DGBL, individually or collaboratively. It is hoped that this study will guide the teachers, policy maker as well as Ministry of Education in identifying the best practises in implementing DGBL in the curriculum, formally and to understand how DGBL can promote highly skilled students, especially in collaborative, creative and innovative environment in the face of the IR4.0 era.